In your eyes only: deficits in executive functioning after frontal TMS reflect in eye movements - Lüthi, Mathias; Henke, Katharina; Gutbrod, Klemens; Nyffeler, Thomas; Chaves, Silvia; Müri, René M. (Frontiers in Behavioral Neuroscience, 2014)
This study investigated the roles of the right and left dorsolateral prefrontal (rDLPFC, lDLPFC) and the medial frontal cortex (MFC) in executive functioning using a theta burst transcranial magnetic stimulation (TMS) approach. Healthy subjects solved two visual search tasks: a number search task with low cognitive demands, and a number and letter search task with high cognitive demands. To observe how subjects solved the tasks, we assessed their behavior with and without TMS using eye movements when subjects were confronted with specific executive demands. To observe executive functions, we were particularly interested in TMS-induced changes in visual exploration strategies found to be associated with good or bad performance in a control condition without TMS stimulation. TMS left processing time unchanged in both tasks. Inhibition of the rDLPFC resulted in a decrease in anticipatory fixations in the number search task, i.e., a decrease in a good strategy in this low demand task. This was paired with a decrease in stimulus fixations. Together, these results point to a role of the rDLPFC in planning and response selection. Inhibition of the lDLPFC and the MFC resulted in an increase in anticipatory fixations in the number and letter search task, i.e., an increase in the application of a good strategy in this task. We interpret these results as a compensatory strategy to account for TMS-induced deficits in attentional switching when faced with high switching demands. After inhibition of the lDLPFC, an increase in regressive fixations was found in the number and letter search task. In the context of high working memory demands, this strategy appears to support TMS-induced working memory deficits. Combining an experimental TMS approach with the recording of eye movements proved sensitive to discrete decrements of executive functions and allows pinpointing the functional organization of the frontal lobes.